2017
DOI: 10.1080/09168451.2017.1359485
|View full text |Cite
|
Sign up to set email alerts
|

Novel squalene-producing thraustochytrids found in mangrove water

Abstract: On extended screening of squalene-producing strains in Okinawa mangrove water, we identified 14 novel squalene-producing thraustochytrids from 172 unialgal clonal isolates. The novel thraustochytrids produced 13.9-7.54 mg squalene/g dry cell weight. Eight isolates were found to belong to potentially novel squalene-producing genera, forming a monophyletic cluster independent from any known thraustochytrids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…MAN70 showed a higher level of squalene production than MAN65, accumulating up to 13 mg/g DW. This accumulation profile is not very different from data published for 132 analyzed isolates, which mostly showed squalene yields between 7.5 and 33 mg/g DW [17,20]. The highest concentrations of squalene were reported in Aurantiochytrium sp.…”
Section: Intracellular Production Of Lipids Protein Carbohydrates contrasting
confidence: 44%
See 1 more Smart Citation
“…MAN70 showed a higher level of squalene production than MAN65, accumulating up to 13 mg/g DW. This accumulation profile is not very different from data published for 132 analyzed isolates, which mostly showed squalene yields between 7.5 and 33 mg/g DW [17,20]. The highest concentrations of squalene were reported in Aurantiochytrium sp.…”
Section: Intracellular Production Of Lipids Protein Carbohydrates contrasting
confidence: 44%
“…Aurantiochytrium species showed the highest concentration of squalene among thraustochytrids, accumulating up to 318 mg/g DW [1,16]. Other representatives of thraustochytrids showed a lower level of squalene production, 0.15-84 g/kg DW [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, A. limacinum displays five times more squalene than its close relative H. fermentalgiana [6]. However, a recent study identified new highly producing strains, forming a distinct clade on a phylogenetic tree and branching out of the Aurantiochytrium cluster [120]. These new thraustochytrid members are potential novel candidates for the commercial production of squalene.…”
Section: Carotenoids Sterols and Squalenementioning
confidence: 99%
“…14 novel squalene producing thraustochytrid strains were isolated and identi ed. The amount of produced squalene was determined between 7.54 to 13.9 g/g CDW [44].…”
Section: Phylogenetic Analysis Of Strain Dr37mentioning
confidence: 99%